Expressions of cenozoic climate changes (Eocene-Oligocene Transition "EOT"; Middle miocene "MMCO, MMCT") in coastal environments highlighted from bivalve geochemistry - Briard, Justine (CCSD, 2020)
The Cenozoic era is characterized by the last transition from a "greenhouse" climate mode to an "icehouse" climate mode with the Antarctic ice-sheet build up. The first traces of glaciation are highlighted at the Eocene-Oligocene Transition (EOT; ~ 33.9 Ma) which is followed by a period of instability of the ice-sheet corresponding to glaciation and deglaciations phases until the terminal glaciation of the Antarctic ice cap during the Middle Miocene Climate Transition (MMCT). However, the processes governing these phases of glaciation-deglaciation remain poorly constrained today and pCO2 fluctuations are not sufficient to explain ice-sheet melting during the Middle Miocene Climate Optimum (MMCO) with pCO2 ranging from 380 to 500 ppm. The main aim of this PhD is to provide new paleoclimatic and paleoenvironmental information during this key period, from coastal environments using a combination of different geochemical proxies, delta(18)O, DELTA(47) and (87)Sr/(86)Sr, measured on bivalve shells. The delta(18)O-DELTA(47) coupling was tested in a variety of environments ranging from restricted environments such as lagoon and bay to open coastal environments. The calculated salinities are in good agreement with the tolerance of the organisms present in the different facies encountered. The results obtained with delta(18)O-DELTA(47) coupling can be used successfully to deconvolve the evolution of temperature and local seawater delta(18)O in brackish to marine environments. The (87)Sr/(86)Sr results could also be linked to runoff activity and for low salinities corresponding to a brackish environment. The new data acquiring for the EOT revealed a 10°C drop in temperatures for the EOT-1 accident in the eastern North Atlantic (England) as well as a salinity drop and a river drainage network modification more affected by the sea level fall occurring during the EOT. A drop of ~8°C was also recorded in open marine environments from western North Atlantic (Florida) during the EOT, associated to an increase in seasonal ...